Relationship of age, body mass index (BMI), physical activity, salt intake, and stress with high blood pressure among rural dwellers in Kudat, Sabah - Khalid Mokti; Syed Sharizman Syed Abdul Rahime (DiscoverSys Inc., 2022)
Background: Hypertension is one of the leading health concerns that can be intervened, especially in rural areas. Thus, this study determined the prevalence and risk factors associated with hypertension among rural dwellers in Kudat’s village, Malaysia. Methods: This study used a cross-sectional design carried out from 5th October 2019 until 17th October 2019. Universal sampling was used for sample size calculation. There are 111 respondents who are above 18 years old involved in this research. Association between hypertension and risk factors outcomes were analyzed by using logistic regression. The relationship between continuous variables was analyzed using correlation analysis. Results: The prevalence of hypertension among Kudat’s villagers was 30% (n=33). There is a significant association between age and BMI with Hypertension. Also, there is a significant correlation between age, BMI, physical activity, with blood pressure. While other risk factors, including sociodemographic and lifestyles, do not significantly correlate with hypertension. Conclusion: Hypertension is highly prevalent in the village and is significantly associated with BMI and age group. Physical activity also correlates with blood pressure. Hence, an effective intervention that includes lifestyle and dietary behavior changes, health promotion, and health screening should be implemented to tackle this problem.